Urban rehabilitation, governance, and housing affordability: lessons from Portugal - Branco, Rosa (2018)
This paper examines the role of ‘urban rehabilitation societies’, a legaland institutional framework launched by the Portuguese government in 2004 and implemented locally ever since. The paper discusses how this model has provided an alibi for neoliberal narratives, grounded on the virtues of the market and on market-oriented strategies. The research methodology uses a combination of qualitative documentary analysis and face-to-face interviews with government officials and public officers to scrutinize the effects of policies on issues of governance and housing affordability.